INVESTIGATING THE REIMBURSEMENT OF PATIENTS WHO DIED WHILE RECEIVING PALLIATIVE CARE ‎SERVICES (Third Sector Social Economic Review, 2024)
Palliative care services have been reimbursed by the Social Security Institution in Turkey for the last ten years. In this descriptive and retrospective study, the Social Security Institution reimbursement amounts of 357 patients who died while receiving palliative care services and the factors affecting the reimbursement amounts were examined. Among the patients included in the study, the proportion of males was 56% (n= 200), the mean age was 76.33±13.46, the mean length of hospitalization was 24.58± 32.16 days, and the median reimbursement amount was ₺5118.9. Patients with pressure injuries and infections were both hospitalized for a statistically significant longer period than those without pressure injuries and infections and were reimbursed at a higher rate. Patients with cancer are hospitalized for shorter periods of time and are reimbursed less than those without cancer. As they are preventable, the presence of infection and pressure injury both indicate a lack of quality of care and lead to increased costs. In regression analysis, infection and type of nutrition (total parenteral nutrition, nasogastric feeding, percutaneous endoscopic gastrostomy) were found to be effective.  To realize the desired service quality and cost reduction, palliative care services should be care-oriented rather than medical treatment-oriented, and service change and diversification should be made by creating new care-oriented units addressing the end of life.
Keywords: Palliative care; reimbursement; social security institution; end of life; health economics